MEKANISME KOPING PSIKO-SPIRITUAL: STUDI FENOMENOLOGI TERHADAP RESILIENSI MAHASISWA PAI DALAM MENGELOLA STRES AKADEMIK - Yudik Pradana; Mashudi; Ubaidillah; Dyah Nawangsari (Irfani, 2026)
This study aims to examine psycho-spiritual coping mechanisms in fostering resilience among students of Islamic Education (PAI) in managing academic stress. The study addresses the growing concern of academic pressure, which affects not only students’ psychological well-being but also their spiritual equilibrium. A qualitative approach with an interpretive phenomenological design was employed to capture the lived experiences of participants. The study involved 8 PAI students from Institut Darul Falah Cermee Bondowoso and Universitas Nurul Jadid Paiton Probolinggo, selected through purposive sampling. Data were collected using semi-structured interviews, participant observation, and document analysis. The findings indicate that students tend to interpret academic stress as a form of spiritual trial and respond by engaging in religious practices such as prayer, dhikr, and reflective contemplation, which contribute significantly to the development of resilience. Furthermore, the socio-religious campus environment plays a crucial role in reinforcing these coping strategies. This study concludes that psycho-spiritual coping is both integrative and context-dependent, offering a meaningful contribution to the discourse of Islamic educational psychology from a phenomenological perspective. The findings underscore the importance of integrating spiritual-based approaches into student mental health services in Islamic higher education settings